2022
DOI: 10.1051/0004-6361/202142778
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of a radio galaxy of at least 5 Mpc

Abstract: Context. Giant radio galaxies (GRGs, or colloquially 'giants') are the Universe's largest structures generated by individual galaxies. They comprise synchrotron-radiating AGN ejecta and attain cosmological (Mpc-scale) lengths. However, the main mechanisms that drive their exceptional growth remain poorly understood. Aims. To deduce the main mechanisms that drive a phenomenon, it is usually instructive to study extreme examples. If there exist host galaxy characteristics that are an important cause for GRG grow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“…Our results are in agreement with Oei et al (2022), who found the largest GRG known to date (LLS=5 Mpc, 𝑧 = 0.25) and it has only 5 galaxies within 10 Mpc, leading to a surface number density of 0.05 Mpc −2 , and does not have a single galaxy within 5 Mpc. The value of the surface number density and the number of the galaxies are similar to those reported in Lan & Prochaska (2021), albeit a direct comparison with their radial profile is impossible as the authors considered only the neighbouring galaxies within a sphere of radius 𝑅 = 1 Mpc centred on the GRG hosts.…”
Section: Grg Environmentsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with Oei et al (2022), who found the largest GRG known to date (LLS=5 Mpc, 𝑧 = 0.25) and it has only 5 galaxies within 10 Mpc, leading to a surface number density of 0.05 Mpc −2 , and does not have a single galaxy within 5 Mpc. The value of the surface number density and the number of the galaxies are similar to those reported in Lan & Prochaska (2021), albeit a direct comparison with their radial profile is impossible as the authors considered only the neighbouring galaxies within a sphere of radius 𝑅 = 1 Mpc centred on the GRG hosts.…”
Section: Grg Environmentsupporting
confidence: 93%
“…In particular, both studies suggest that the jets of GRGs expand into regions that are relatively sparsely populated by galaxies. Machalski et al (2008) argued that a combination of a low-density environment and jet speeds of about 0.1c -0.2c has led to the formation of J1420-0545 which is now the second largest GRG known (Oei et al 2022) with a linear size of 4.69 Mpc.…”
Section: Introductionmentioning
confidence: 99%
“…and study statistical samples of RL sources even at the highest redshifts (z > 6), where only a small number of RL active galactic nuclei (AGNs) have been found so far (see e.g., Table 6 in Bañados et al 2021). The systematic characterisation of these objects, such as their spectral shape and their short-and longterm variability, will provide unique information on the first phases of the launch and propagation of relativistic jets from young SMBHs (e.g., Nyland et al 2020) and their connection with the powerful large-scale radio galaxies observed in the local Universe (e.g., Alexander 2000;Oei et al 2022).…”
Section: Introductionmentioning
confidence: 96%
“…While the inclination angle and the bulk velocities both determine the jet/counter-jet ratio, we make some assumptions about the inclination angle since GRS J0844+4627 is a giant radio galaxy. The size of the largest known giant radio galaxy is ∼ 5 Mpc (Oei et al 2022). If the deprojected size of GRS J0844+4627 is also 5 Mpc then the inclination angle would be 26 • .…”
Section: Interpretation Of the Observationsmentioning
confidence: 99%